Management strategies for implementing a multicenter cross-sectional study: lessons from the ADHERE Brazil study - Elisa Oliveira Marsicano-Souza; Fernando Antônio Basile Colugnati; Barbara Bruna Abreu de Castro; Maria do Socorro Van Keullen; Sabina De Geest; Helady Sanders-Pinheiro (São Paulo Medical Journal, 2022)
ABSTRACT BACKGROUND: Epidemiological studies involving large samples usually face financial and operational challenges. OBJECTIVES: To describe the planning and execution of ADHERE Brazil, an epidemiological study on 1,105 kidney transplant patients, and report on how the study was structured, difficulties faced and solutions found. DESIGN AND SETTING: Cross-sectional multicenter study in 20 Brazilian kidney transplantation centers. METHODS: Actions developed in each phase of implementation were described, with emphasis on innovations used within the logistics of this study, aimed at estimating the prevalence of nonadherence to treatment. RESULTS: Coordination of activities was divided into four areas: general, regulatory, data collection and statistics. Weekly meetings were held for action planning. The general coordination team was in charge of project elaboration, choice of participating centers, definition of publication policy and monitoring other coordination teams. The regulatory team provided support to centers for submitting the project to ethics committees. The data collection team prepared a manual on the electronic collection system, scheduled web meetings and was available to respond to queries. It also monitored the data quality and reported any inadequacies found. Communication with the centers was through monthly reports via e-mail and distribution of exclusive material. The statistical team acted in all phases of the study, especially in creating the data analysis plan and data bank, generation of randomization lists and data extraction. CONCLUSIONS: Through these logistics, we collected high-quality data and built a local research infrastructure for further studies. We present supporting alternatives for conducting similar studies. CLINICAL TRIAL ANNOTATION: http://clinicaltrials.gov/ on October 10, 2013; NCT02066935.